Coupled Surface-Confinement Effect and Pore Engineering in a Single-Fe-Atom Catalyst for Ultrafast Fenton-like Reaction with High-Valent Iron-Oxo Complex Oxidation - Bingkun Huang; Zelin Wu; Xinhao Wang; Song, Xinyu; Hongyu Zhou; Heng Zhang; Peng Zhou; Liu, Wen; Zhaokun Xiong; Bo Lai (Environmental Science & Technology, 2023)
The nanoconfinement effect in Fenton-like reactions shows great potential in environmental remediation, but the construction of confinement structure and the corresponding mechanism are rarely elucidated systematically. Herein, we proposed a novel peroxymonosulfate (PMS) activation system employing the single Fe atom supported on mesoporous N-doped carbon (FeSA-MNC, specific surface area = 1520.9 m2/g), which could accelerate the catalytic oxidation process via the surface-confinement effect. The degradation activity of the confined system was remarkably increased by 34.6 times compared to its analogue unconfined system. The generation of almost 100% high-valent iron-oxo species was identified via 18O isotope-labeled experiments, quenching tests, and probe methods. The density functional theory illustrated that the surface-confinement effect narrows the gap between the d-band center and Fermi level of the single Fe atom, which strengthens the charge transfer rate at the reaction interface and reduces the free energy barrier for PMS activation. The surface-confinement system exhibited excellent pollutant degradation efficiency, robust resistance to coexisting matter, and adaptation of a wide pH range (3.0–11.0) and various temperature environments (5–40 °C). Finally, the FeSA-MNC/PMS system could achieve 100% sulfamethoxazole removal without significant performance decline after 10,000-bed volumes. This work provides novel and significant insights into the surface-confinement effect in Fenton-like chemistry and guides the design of superior oxidation systems for environmental remediation.